Responsibility in Public Administration Ethics. (18th January 2018) - Plant, Jeremy F.
Abstract : The principle that public administrators act in a responsible manner has been fundamental to the development of the field of public administration as a profession and scholarly discipline since its inception. Administrative responsibility is seen as the glue that connects administrative ethics to the more general questions regarding the proper role and behavior of unelected officials in a democratic system. In the past two decades, explicit and implicit considerations of responsibility continue to be significant factors in the continuing evolution of public sector ethics, thereby providing a normative and descriptive base upon which more specific topics, such as corruption, integrity of governance, public values, and social equity, can be examined in a balanced manner.